STEM-INTEGRATED PROJECT BASED LEARNING (PJBL) LEARNING TOOLS TO IMPROVE ELEMENTARY SCHOOL STUDENTS' CREATIVE THINKING SKILLS - Angelina K. Sinaga; Harun Sitompul; Efendi Napitupulu (RADJA PUBLIKA, 2025)
Integrated STEM-based Project-Based Learning (PjBL) is an instructional approach designed by teachers to actively engage students in learning activities, aiming to enhance their creative thinking skills and stimulate the exploration of new ideas. This study aimed to analyze the feasibility, effectiveness, and practicality of STEM-integrated PjBL learning devices in improving the creative thinking skills of fourth-grade students at Santo Paulus Martubung Elementary School, Medan. The research employed a Research and Development (R&D) method. The findings indicated that the developed learning devices significantly improved students' creative thinking skills, as evidenced by an average n-gain score of 0.49, which falls into the moderate improvement category. Additionally, the devices proved effective in enhancing students' scientific literacy, with an average score of 0.64, also categorized as a moderate increase. The observed improvements included greater interest in science and technology, active participation in discovery-based activities (practices and projects), and a stronger sense of responsibility in managing natural resources and the surrounding environment. Therefore, the STEM-integrated PjBL learning devices are considered feasible, effective, and practical for use in primary education, supporting contextual learning that fosters students’ creative thinking and scientific literacy.